THE INTERPRETATION OF THE COMMANDER OF THE UZBEK MOUNTAIN CAVALRY DIVISION MIRKOMIL MIRSHAROPOV IN WORKS OF ART (Scientific journal of the Fergana State University, 2024)
The article examines the history of the Uzbek mountain-cavalry division, its establishment, and its role in the history of military work in Uzbekistan. Also, in the article, the importance of works of art such as fiction, film, and paintings in illuminating historical figures and processes, the interpretation of the image of Mirkomil Mirsharopov, the only commander of the Uzbek mountain-cavalry division, who belongs to the famous Uzbek nationality, in works of fiction, cinema, art, and paintings, the artistic and its embodiment in cinematographic works and painting samples is analyzed.